دراسة العلاقة بين نقصان مستويات CA19-9 أثناء العلاج الكيميائي وتحسن معدل البقيا لدى مرضى أورام البنكرياس المتقدمة (خبرة مشفى تشرين الجامعي في اللاذقية بين عامي 2014-2015) - زحلوق نديم; اسبر ليانة (Latakia University Journal -Medical Sciences Series, 2017)
أثبتت الدراسات وجود قيمة إنذارية للواسم الورمي CA19-9 بعد الجراحة لدى مرضى سرطانة البنكرياس القابلين للجراحة .الهدف من دراستنا هو معرفة فيما إذا كان لهذا الواسم نفس القيمة الإنذارية لدى مرضى سرطانة البنكرياس المتقدمة غير القابلة للجراحة و الذين خضعوا للعلاج الكيماوي . بين شهري أذار 2014 وكانون الأول 2015 ، خضع 36 مريض (متوسط العمر 57 سنة ، تراوحت الأعمار بين 38-80 سنة ، 9 إناث ،27 ذكور ) لديهم سرطانة بنكرياس غدية متقدمة موضعياً أو نقائلية مع مشعر karnofsky أكبر أو يساوي 60 للعلاج الكيماوي. فقط المرضى ذوي قيمة الواسم المرتفعة مع قيمة البيليروبين أقل من 2 ملغ/دل هم من أدخلوا في الدراسة. تم قياس البقيا اعتباراً من القيمة الأولى للواسم الورمي بعد العلاج و حتى الوفاة أو حتى أخر متابعة . تبين أن كانت معدلات البقيا الوسطية لدى المرضى الذين انخفض لديهم الواسم CA19-9 أكثر من 20% من القيمة القاعدية بعد 8 أسابيع من العلاج أفضل بفارق هام إحصائياً عن البقيا لدى بقية المرضى ( 6.98 مقابل 4.68 شهر ، P=0.007). في حين لم يشكل العمر و قيمة الواسم البدئية عوامل مستقلة في التأثير على البقيا ( P=0.987 ،P=0.878 على التوالي ). كانت البقيا أفضل عند الإناث منه عند الذكور بفارق هام إحصائياً ( 7.83 مقابل 5.75 شهر ، P=0.023 ). Studies demonstrated a prognostic role for postoperative CA 19-9 in patients with resectable pancreatic carcinoma following surgery. Our study aimed to investigate whether CA 19-9 provided similar prognostic information in patients with advanced unresectable pancreatic cancer treated with chemotherapy and to determine whether such endpoints should therefore be reported in future randomized trials. Between Mars 2014 and December 2015, 36 patients ( median age 57 years, range 38-80 years, 9 females, 27 males ) with locally advanced or metastatic pancreatic adenocarcinoma and a baseline Karnofsky-index more than 60 were treated with chemotherapy . Only patients with a bilirubin of less than 2 mg/dL at the time the CA 19-9 was evaluated were included in the analysis to avoid the confounding effect of hyperbilirubinemia. Only patients with basal high CA19-9 were included in the analysis. Survival was measured from the date of first post CRT CA 19-9 level until death or last follow-up. Patients with a decrease of20 < % of the baseline CA19-9 level after 8 weeks of treatment (n=25) had a significantly better median survival than patients with a rise or a decrease< 20% (n-11) (6.98 vs4.68 months; p=0.007). Age and basal CA19-9 did not show significant or a trend for significant differences regarding survival by univariate analysis (P=0.987, p=0.878 respectively). Females had a significantly better median survival than males (7.83 vs 5.75 months, P=0.023).